Superficial siderosis of central nervous system with unknown cause: report of 2 cases and review of the literature. (4th May 2019) - Chen, Hao; Raza, Hafiz Khuram; Jing, Jia; Ye, Xinchun; Zhang, Zuohui; Hua, Fang; Cui, Guiyun
Abstract: Objective: To report 2 cases of superficial siderosis of central nervous system (SS-CNS) and a review of the literature. Methods: We have analyzed the clinical data and relevant features of two patients with SS-CNS who were presented with ataxia and slurred speech. Both patients undertook blood tests, lumbar puncture, head CT (computer tomography) scans, and brain and spinal cord magnetic resonance (MR) scans. In addition, the first patient also undewent enhanced susceptibility-weighted angiography (ESWAN) and the second patient undertook susceptibility weighted imaging (SWI) scan. We searched PubMed with the keywords superficial siderosis and superficial siderosis of central nervous system, and selected publications that seemed appropriate. Results: A neurological examination revealed bilateral sensorineural hearing impairment in both the patients. Their past history was not significant to identify hemorrhage. Brain MR scans demonstrated typical hypointensity rimming at the brain surface on T2 weighted images. The patients were diagnosed with SS-CNS. Conclusion: SS-CNS should be highly suspected in patients with progressive sensorineural hearing loss, ataxia, and signs of pyramidal tracts, and MR scans of brain and whole spinal cord should be undertaken to confirm the diagnosis. Advanced MRI techniques such as SWI and ESWAN are helpful in making the diagnosis of SS-CNS. The cause of hemorrhage is not identified in most cases.